Differential susceptibility of Red Sea Pocilloporidae corals to UVB highlights photoacclimation potential - Overmans, Sebastian; Agustí, Susana (Frontiers in Marine Science, 2023)
Despite being exposed to extreme water temperatures and solar irradiances, Red Sea corals are relatively resistant to bleaching. While their thermal tolerance is well described, little is known about their resistance to ultraviolet-B radiation (UVB). Here, we performed a short-term (2 days) UVB-removal incubation with Stylophora pistillata, and in situ measurements with Pocillopora verrucosa complemented by a long-term (46 days) transplantation and UVB-removal experiment. Using a suite of physiological parameters (effective quantum yield (Fv’/Fm’), oxidative stress (lipid peroxidation, LPO), and primary production), we assessed the impacts of UVB on the physiology and acclimation capacity of Red Sea corals. Shielding S. pistillata from UVB did not change the gross primary production or Fv’/Fm’, and respiration and LPO in the host remained unaffected. In situ, P. verrucosa exhibited less varying and significantly higher Fv’/Fm’ in 8 m depth (0.61 ± 0.04) than in 4 m (0.52 ± 0.06), 2 m (0.51 ± 0.09), and 0.5 m (0.50 ± 0.11), where water temperatures ranged from 30.5–33.4, 30.6–34.0, 30.8–34.5, 30.6–37.3°C and daily UVB exposures averaged 0.9, 2.9, 11.8 and 21.4 kJ m-2, respectively. Fv’/Fm’ correlated the strongest with UVB (-0.57), followed by PAR (-0.54) and temperature (-0.40), suggesting that UVB is a key determinant of photosynthetic efficiency. Fv’/Fm’ of upward transplanted specimens (T 1m) was initially decreased but gradually increased and reached the same values as shallow corals (1 m) after 44 days. UVB removal significantly increased the Fv’/Fm’ of transplanted corals in the first 20 days. Oxidative stress was initially highest in T 1m samples under full sunlight but equalized with 1 m specimens by day 46, whereas oxidative stress was significantly reduced by day 4 in T 1m corals sheltered from UVB. Overall, UVB-removal generally had little impact on the physiology of shallow-water S. pistillata and P. verrucosa but considerably accelerated the acclimation of upward transplanted corals. Our study highlights that UVB is a crucial stressor governing the photoacclimation capacity of these Red Sea coral species.